Effects of ground cover from branches of arboreal species on weed growth and maize yield (Revista Ciência Agronômica, 2015)
Cultivating maize under systems of alley cropping results in improvements to the soil, a reduction inweeds and an increase in yield. Studies using ground cover from tree shoots produce similar results. The aim of thisstudy was to evaluate the effects on weed growth and maize yield of ground cover made up of 30 t ha-1 (fresh matter)of branches from the tree species: neem (Azadirachta indica A. Juss), gliricidia [Gliricidia sepium (Jacq.) Kunth exWalp.], leucaena [Leucaena leucocephala (Lam.) de Wit.] and sabiá (Mimosa caesalpiniifolia Benth.). Two treatmentgroups (cultivars and weed control) were evaluated. The cultivars AG 1041 and AL Bandeirantes were subjected to thefollowing treatments: no hoeing, double hoeing, and ground a cover of branches of the above species when sowing themaize. A randomised block design was used with split lots (cultivars in the lots) and ten replications. The cultivars didnot differ for green ear or grain yield. Double hoeing was more effective than ground cover at reducing the growth ofweeds. However, both weeding and ground cover resulted in similar yields for green ears and grain, which were greaterthan those obtained with the unweeded maize.